OsDXR interacts with OsMORF1 to regulate chloroplast development and the RNA editing of chloroplast genes in rice - Peng-hui CAO; Di WANG; Su GAO; Xi LIU; Zhong-ying QIAO; Yu-lin XIE; Ming-hui DONG; Tan-xiao DU; Xian ZHANG; Rui ZHANG; Jian-hui JI (Journal of Integrative Agriculture)
Plant chlorophyll biosynthesis and chloroplast development are two complex processes that are regulated by exogenous and endogenous factors. In this study, we identified OsDXR, a gene encoding a reductoisomerase that positively regulates chlorophyll biosynthesis and chloroplast development in rice. OsDXR knock-out lines displayed the albino phenotype and could not complete the whole life cycle process. OsDXR was highly expressed in rice leaves, and subcellular localization indicated that OsDXR is a chloroplast protein. Many genes involved in chlorophyll biosynthesis and chloroplast development were differentially expressed in the OsDXR knock-out lines compared to the wild type. Moreover, we found that the RNA editing efficiencies of ndhA-1019 and rpl2-1 were significantly reduced in the OsDXR knock-out lines. Furthermore, OsDXR interacted with the RNA editing factor OsMORF1 in a yeast two-hybrid screen and bimolecular fluorescence complementation assay. Finally, disruption of the plastidial 2-C-methyl-derythritol-4-phosphate pathway resulted in defects in chloroplast development and the RNA editing of chloroplast genes.